Family dinner - Gan, Clara Li Juan (2012)
Family Dinner is a 2D-animated short film that digs humour at role reversal in the family. Househusband bunny-dad is dissatisfied with family life. He is unable to control his children’s antics, and feels incompetent as a father and a husband. Finding a family recipe for fathers in a magazine, he prepares a dinner and cleans the house, hoping to create the illusion of the perfect family and to get reconnected with and impress his wife. However, the happy dinner is destroyed, but he eventually realises that he loves his family anyway. In this report, I will discuss the ideas behind the project, the influences that shaped the project and the work process behind the animation.